Cenozoic structural evolution of the Andaman Sea: Evolution from an extensional to a sheared margin - C. K. Morley (2018)
© 2016 The Author(s). Published by The Geological Society of London. The Andaman Sea is proposed to have developed from a margin where Palaeogene back-arc collapse closed a mid-Cretaceous back-arc oceanic basin, and resulted in the collision between island arc crust to the west and the western margin of Sundaland. Subsequent east- west to WNW-ESE extension during the Late Eocene-Oligocene resulted in highly extended continental crust underlying the Alcock and Sewell rises, and the East Andaman Basin, and moderately extended crust in the Megui-North Sumatra Basin. As India coupled with western Myanmar, the margin became dominated by dextral strike-slip and NNW-SSE transtensional deformation during the Miocene. The narrow belt of NNW -SSE-directed extension is proposed to have focused on the region where ductile middle crust remained following Late Eocene- Oligocene extension, whereas strike-slip faults are located in the regions of necking where ductile middle crust was considerably thinned by Late Eocene-Oligocene extension. The last phase of NNW-SSE-extension switched between probable Late Miocene-Early Pliocene seafloor spreading, and extension (by dyke intrusion and faulting) in the Alcock and Sewell rises, and then recently back to the spreading centre.